Persistent Primitivisms: Popular and Academic Discourses about Pacific and Māori Cinema and Television - Pearson, Sarina (Waka Kuaka, 2013)
Despite the sophistication of international audiences and the politically subversive work produced by postcolonial creatives in the Pacific, romanticism continues to profoundly shape critical discourses about film and television set in the South Pacific. This article examines how the criticism generated (and sometimes not generated) in academic studies and among film critics reflects persistent discourses of primitivism. Even politically progressive narratives find themselves subject to the gravity of romanticism. The sheer persistence of these assumptions that continue to cast Pacific subjects as timeless, innocent and primitive remind us of the resilience of what Trouillot calls "the Savage slot" (1991, 2003).